2017
DOI: 10.1111/jmg.12285
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure metamorphic evolution of eclogite and associated metapelite from the Chuacús complex (Guatemala Suture Zone): Constraints from phase equilibria modelling coupled with Lu‐Hf and U‐Pb geochronology

Abstract: As is common in suture zones, widespread high‐pressure rocks in the Caribbean region reached eclogite facies conditions close to ultrahigh‐pressure metamorphism. Besides eclogite lenses, abundant metapelitic rocks in the Chuacús complex (Guatemala Suture Zone) also preserve evidence for high‐pressure metamorphism. A comprehensive petrological and geochronological study was undertaken to constrain the tectonometamorphic evolution of eclogite and associated metapelite from this area in central Guatemala. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 107 publications
(205 reference statements)
1
4
0
Order By: Relevance
“…Depletion of grossular in the garnet rims is interpreted to be an effect of the zoisite‐in reaction along the retrograde part of the P–T path. A similar pattern has been observed in kyanite‐eclogites elsewhere, for example, in the Tromsdalstind eclogite of the Scandinavian Caledonides (Janák, Ravna, & Kullerud, ) and in the Chuacús complex of the Guatemala Suture Zone (Maldonaldo, Weber, Ortega‐Gutierréz, & Solari, ). This second generation of zoisite commonly overgrows omphacite and occurs in contact with the garnet rims.…”
Section: Discussionsupporting
confidence: 73%
“…Depletion of grossular in the garnet rims is interpreted to be an effect of the zoisite‐in reaction along the retrograde part of the P–T path. A similar pattern has been observed in kyanite‐eclogites elsewhere, for example, in the Tromsdalstind eclogite of the Scandinavian Caledonides (Janák, Ravna, & Kullerud, ) and in the Chuacús complex of the Guatemala Suture Zone (Maldonaldo, Weber, Ortega‐Gutierréz, & Solari, ). This second generation of zoisite commonly overgrows omphacite and occurs in contact with the garnet rims.…”
Section: Discussionsupporting
confidence: 73%
“…While Cretaceous metamorphism has been reported for the eastern segment of the Polochic‐Motagua fault system, the data presented here are potentially the first record of this event in the western segment. The closest locality with a similar Cretaceous age is therefore ~200 km to the east along the Polochic Fault within the high‐pressure metamorphic Chuacús Complex of Guatemala (see Figure 1b; Maldonado, Weber, et al, 2018; Martens et al, 2012; Ratschbacher et al, 2009). The timing of eclogite facies metamorphism in the Chuacús Complex has been dated with the Lu‐Hf method on garnet and whole‐rock aliquots from eclogite at 101 ± 3 and 95 ± 2 Ma, whereas zircon, monazite and titanite U–Pb ages indicate later‐stage events at c. 80–74 Ma (Maldonado, Weber, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The closest locality with a similar Cretaceous age is therefore ~200 km to the east along the Polochic Fault within the high‐pressure metamorphic Chuacús Complex of Guatemala (see Figure 1b; Maldonado, Weber, et al, 2018; Martens et al, 2012; Ratschbacher et al, 2009). The timing of eclogite facies metamorphism in the Chuacús Complex has been dated with the Lu‐Hf method on garnet and whole‐rock aliquots from eclogite at 101 ± 3 and 95 ± 2 Ma, whereas zircon, monazite and titanite U–Pb ages indicate later‐stage events at c. 80–74 Ma (Maldonado, Weber, et al, 2018). Zircon dating of meta‐granitoids associated with eclogites showed protolith ages of c. 1.1–1.0 Ga and c. 224 Ma (Maldonado, Ortega‐Gutiérrez et al, 2018; Solari et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onset of back‐arc closure could have initiated as early as the Barremian (Bandini et al, ), as suggested by the formation of the North Motagua Mélange (Harlow et al, ; Brueckner et al, ; Flores et al, ; Figures c and c). At the junction between the Arperos and proto‐Caribbean basins, back‐arc closure led to the subduction of the Maya Block (Bandini et al, ; Flores et al, ) thus forming the Chuacús Complex (approximately 100‐Ma metamorphic peak; Maldonado et al, ; Figures d and d). The restriction of metamorphic events to the southern part of the back‐arc suggests that the basin was significantly wider in its southern segment, possibly due to the proximity of the spreading proto‐Caribbean oceanic floor, thus allowing for further shortening to occur during subsequent back‐arc closure (Figures and ).…”
Section: Margin‐scale Geodynamic Scenariomentioning
confidence: 99%